2013
DOI: 10.1002/mar.20591
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Influences on Children's Food Consumption

Abstract: This exploratory study generated a grounded theory of factors influencing children's diets, particularly those that contribute to suboptimal eating and ultimately child obesity. The study involved 124 children (aged 6–12 years) and 39 of their parents from three separate junior schools (including a lower, middle, and higher socioeconomic school). Research methods included (i) interviews with children and parents and (ii) observations, drawings, and lunchbox audits with children. The findings suggest that child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 59 publications
1
37
0
5
Order By: Relevance
“…Many of the parents in the present study were living without a partner, and all were on low incomes; therefore, food was an inexpensive way to physically demonstrate love and to feel love in return. A similar finding has been reported elsewhere, 31 with the gifting of unhealthy foods being more prevalent in lower SES families and used as a way of compensating for loss of time with a parent or deprivation of material possessions.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Many of the parents in the present study were living without a partner, and all were on low incomes; therefore, food was an inexpensive way to physically demonstrate love and to feel love in return. A similar finding has been reported elsewhere, 31 with the gifting of unhealthy foods being more prevalent in lower SES families and used as a way of compensating for loss of time with a parent or deprivation of material possessions.…”
Section: Resultssupporting
confidence: 88%
“…It is also possible that, due to their socioeconomic circumstances, this study's parents may not have had other avenues for treating their children with more expensive items, thus more emphasis may have been placed on the use of food as a treat, as per Roberts and Pettigrew. 31 The influence of society and the expectation to provide children with treat foods was also common in Petrunoff et al's study, 8 and was expressed by parents from both low and high SES groups. The myriad food advertisements promoting the use of sweet treats to signify parental love 33 might be negatively impinging on parents' treating behaviours and their children's subsequent weight status.…”
Section: Resultsmentioning
confidence: 92%
“…This study emerges from data obtained through photo elicitation interviews and focus group discussions (FGDs) with 30 mothers of primary school children. Participants with children aged 9-11 were recruited, since at this age children can negotiate their food preferences with their parents (Roberts and Pettigrew 2013). Participants were mainly recruited from two primary schools, a rural Surrey school in a wealthy, white middle class catchment area and an urban West London school in a more diverse catchment area in ethnic and social class terms.…”
Section: Methodsmentioning
confidence: 99%
“…A second study showed that eye contact with cereal spokes-characters increased feelings of trust, connection, and choice (Musicus, Tal, & Wansink, 2014). Although the eyes of a spokesperson might also be used for more effectively selling healthier food, specific care should be taken when such foods are focused toward younger children (Roberts & Pettigrew, 2013).…”
Section: More Attractive To Selectmentioning
confidence: 99%